CSC658: Computer Graphics / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
Graphics is one of the most important elements in multimedia. Therefore, a study in multimedia would be incomplete without the study of computer graphics. This course will provide the students with the necessary knowledge on computer graphics such as concept, theory of computer graphics and colors and hardware devices required to produce a graphics. Basic scientific visualization and animation techniques will also be presented in this course.